ממן17

ממן17 - 17 " :...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 17 " : .14.02.2006 , ' 1 . A, B - . ,I-1 ,I-2 . 1 - B - A - . . ,I-4 ,B - A - C . C - , 1 . 1 C - , 1 .( B - A - ) B - A AB - . C - A ,I-2 . 2 - , C , 2 - . a1 - , A .1 a1 C D a1 , 1 C . 1 - C ,III-1 . CD AB D B - D . a1 , D , ) ,C 1 2 A ,A - D .( , . a1 A - a1 D . 1 D - 1 B B - D . AB CD - A, B, C , D 4 .' A, B, C , D .(ABE ) E ,II-4 . AE CF F a1 ,III-1 : D F - .2 . AE CD , . D - F - , CD > AB , . AE > AB , ( ABE ) . D - F . , CD AB ,' ,II-3 . C , D, F : . (CDF ); (CFD ); ( DCF ); ( DFC ); ( FCD); ( FDC ) , C , a1 D F : .C . (CDF ); (CFD ); ( DFC ); ( FDC ) (DFC ) ,II-1 F . (CFD) , (CFD) : (DFC ) CD > CF , . (CFD) , AE CF ,F . . CD > AE , . AE = CF A B E , ( ABE ) ,E , AB CD ,' . AE > AB a1 C D 1 2 , . AE > CD , . AB = CD , . AE > CD CD > AE . (CDF ); ( FDC ) , ( DFC ); (CFD ) , ,II-1 . , AE CF - ( ABE ) . (CDF ) 2 , bc = (ta + r )(ua + s) = = tua 2 + sta + rua + rs = = (tua + st + ru )a + rs .1 . : , . c = ua + s b = ta + r - t, u , tua + st + ru : . k N , k = tua + st + ru . bc = ka + rs a - bc , , , rs < a , rs , . , ."" : , r = 1, s = 2 , a = 2, b = 1, c = 3 . rs < a , 2 < 2 , a = 2 - , rs = 1 2 = 2 . . b = ta + r , . r < a - : , b 2 = (ta + r ) 2 b 2 = t 2 a 2 + 2tar + r 2 b 2 = (t 2 a + 2tr )a + r 2 , t 2 a + 2tr : , m N , m = t 2 a + 2tr . b 2 = ma + r 2 : r< a r2 < a a - b 2 , . ,"" . r 2 , . 6 .3 .2 p p2 . 2 = 6 , = 6 ; p, q Z , q 0 , q q , . 0 6 = 0 - , p 2 = 0 , p = 0 . p 0 : q 2 > 0 p 2 > 0 q 2 < 0 p 2 > 0 q 2 > 0 p 2 < 0 .i .ii .iii q 2 < 0 p 2 < 0 .iv , 6 , ii ii , 6 , . . iii , . , iv . . p, q , p 2 , q 2 , , p 2 , q 2 , . p2 =6 q2 p 2 = 6q 2 p2 = 2 3 q2 p 2 = 2 (3q 2 ) , 2 | p 2 , . , 3q 2 n 2 , p . 2 | p , p 2 = (2 n m) 2 = 2 2 n m 2 , . m, n N - p = 2 n m , . 2 , p 2 2 , 2 | q 2 2 , q 2 . , q 2 .0 - 2 ,- 2 . 2n + 1 , 2 (3q 2 ) . p 2 = 2 (3q 2 ) , p 2 , , - 2 , , . - , , 6 . 3 p q , A = 2 3 | p, q N 0 A - - { } .1 .0 p, q + , A = { 2m + 3n | m, n N 0 } A - - .0 m, n , 3 | x , . q 0 , p = 0 .( x = 2 p 3 q ) x A q -1 , x = 2 0 + 3 3 q -1 , x A + . 3 3 q -1 = x 3 N 0 - , m = 0, n = 3 q -1 : A + - .0- , m, n N 0 p -1 . 2 2 p -1 = x 2 N 0 , 2 | x , p > 0 , m, n N 0 - , m = 2 p -1 , n = 3 q -1 . x = 2 2 p -1 + 3 3 q -1 , x A + .0- x A * . x A + q > 0 q = 0 . A A + , x A + 5- , 5 = 2 1 + 3 1 : 5 A + , . x A - x A + . 5 = 2 p 3 q - p, q N 0 ,3 2 . A A + , 1 p B = , 2 q 1 | p, q N 0 B - - 3 .2 .0 p, q 1 1 + , B = m + n | m, n N 0 B - - 3 2 .0 m, n 1 . 2 1 1 1 1 + = : x B + - x B , B / B 6 3 1 + m, n N 0 , B - 6 1 1 1 : . m + n = ,0 6 2 3 m n 1 + = 2 3 6 3m + 2n = 1 m, n - , : , m = 1, n = 0 m = 0, n = 1 , 3m + 2n = = 3 0 + 2 1 = = 2 >1 3m + 2n = = 3 1 + 2 0 = = 3 >1 , 3m + 2n > 1 3(m + 1) + 2n = = 3m + 3 + 2n = = (3m + 2n) + 3 > 3m + 2n > 1 , 3m + 2( n + 1) = = 3m + 2n + 2 = = (3m + 2n) + 2 > 3m + 2n > 1 1 + . B , 6 5 1 1 . 1 + 1 = : x B - x B + , B + / B 6 2 3 p, q N 0 , 5 1 1 : . = - ,0 6 2 3 1 5 = q 6 2 3 p q 5(2 3 ) =1 6 5 2 p 3q =1 23 5 2 p -1 3 q -1 = 1 p p q , p, q - , : , p = 1, q = 0 p = 0, q = 1 5 2 p -1 3 q -1 = = 5 2 -1 3 0 = 1 = 5 1 = 2 1 = 2 >1 2 5 2 p -1 3 q -1 = = 5 2 0 3 -1 = 1 = 5 1 = 3 2 =1 >1 3 5 2 p -1 3 q -1 > 1 , 5 2 ( p +1) -1 3 q -1 = = 5 2 p 3 q -1 = = (5 2 p -1 3 q -1 ) 2 > 5 2 p -1 3 q -1 > 1 5 2 p -1 3 ( q +1) -1 = = 5 2 p -1 3 q = = (5 2 p -1 3 q -1 ) 3 > 5 2 p -1 3 q -1 > 1 5 . B , , 6 p q k , C = 6 15 35 | p, q, k N 0 C - - { } .3 .0 p, q, k 2 | n 7 | n - , 2 | 14 7 | 14 . 14 | n n C - . ) 6 | n, 15 | n, 35 | n : 7 | n .(0- p, q, k . 35 | n ,35 7 C - . 6 | n ,6 2 C - , 2 | n - . 3 | n , 3 | 6 6 | n ; 5 | n , 5 | 35 35 | n . (3 5 = 15) | n , 15 | n - 14 | n n C - . 4 : , ,3 , 1 1 1 + + = 3 +1 3 + 2 2 3 1 1 1 = + + = 4 5 6 47 3 = > 60 5 . k + 1 - , k , : 1 1 1 1 3 + + ++ > k +1 k + 2 k + 3 2k 5 : 1 1 1 + - 2k + 1 2k + 2 k + 1 .1 1 1 1 1 1 1 1 1 3 + ++ + + > + - + k +2 k +3 2 k 2 k + 1 2 k + 2 2 k + 1 2k + 2 k + 1 5 1 1 1 1 1 1 1 1 3 + + + + + > + - + (k + 1) + 1 (k + 1) + 2 2(k + 1) - 2 2(k + 1) - 1 2(k + 1) 2k + 1 2k + 2 k + 1 5 1 1 1 1 1 1 3 + + + > + - + (k + 1) + 1 (k + 1) + 2 2(k + 1) 2k + 1 2k + 2 k + 1 5 : 1 1 1 + - > 0 2k + 1 2k + 2 k + 1 = = = = 1 1 1 + - = 2k + 1 2k + 2 k + 1 1 1 1 + - = 2k + 1 2( k + 1) k + 1 2(k + 1) + (2k + 1) - 2(2k + 1) = 2(2k + 1)(k + 1) 2k + 2 + 2k + 1 - 4k - 2 = 4k 2 + 6 k + 2 1 2 4k + 6k + 2 , 1 > 0 . k > 0 , k 4k + 6k + 2 2 , , 1 1 1 + - > 0 , . 2k + 1 2k + 2 k + 1 1 1 1 3 3 + - + > 2k + 1 2k + 2 k + 1 5 5 : 1 1 1 1 1 1 3 + + + > + - + (k + 1) + 1 (k + 1) + 2 2(k + 1) 2k + 1 2k + 2 k + 1 5 : 1 1 1 3 + + + > (k + 1) + 1 (k + 1) + 2 2(k + 1) 5 . k - ; k + 1 - . n 3 , : n = 1 - , an -1 = = a1 - 1 = = a -1 . n = 1 a - 1 | a n - 1 , , a - 1 | a - 1 , k : k + 1 - : t . a - 1 | a k - 1 ( a 0 a > 1 ; a - ) ( a - 1 ) ( ) u , ta + 1 = u k : ,( t - , a t (a - 1) = a - 1 ) . u (a - 1) = a k +1 .(- ) .1 .2 -1 ta (a - 1) = a k +1 - a ta (a - 1) + a - 1 = a k +1 - 1 (ta + 1)(a - 1) = a k +1 - 1 . a - 1 | a k - 1 - , a - 1 | a k +1 - 1 , . n , : n = 1 - a 2 n -1 + 1 = ( n = 1 ) = a1 + 1 = = a +1 .2 . , a + 1 | a + 1 - a + 1 | a 2 k -1 + 1 , k . a + 1 | a 2 ( k +1) -1 + 1 : t , ( a 0 - ) ( - a + 1 ) t (a + 1) = a 2 k -1 + 1 ( ) ta(a + 1) = a 2 k + a , , ta -1 = u : ta(a + 1) - a + 1 = a 2 k +2-2 + 1 (ta - 1)(a + 1) = a 2( k +1) -2 + 1 . a 2 , a - a > 1 . t 1 , t , ta - 1 . ta - 1 1 : ,1 , ta 2 : u , . ta - 1 , . a + 1 | a 2 ( k +1) -2 + 1 , u (a + 1) = a 2( k +1) - 2 + 1 , , a + 1 | a 2 ( k +1) -1 + 1 - - a, n , . a + 1 | a 2 n -1 + 1 a > 1 ...
View Full Document

Ask a homework question - tutors are online